Altered Lung Microbiome and Metabolome Profile in Children With Pulmonary Arterial Hypertension Associated With Congenital Heart Disease - Ma, Runwei; Cheng, Liming; Song, Yi; Sun, Yi; Gui, Wenting; Deng, Yao; Xie, Chao; Liu, Min (Frontiers in Medicine, 2022)
Backgrounds Pulmonary arterial hypertension (PAH) is characterized by progressive pulmonary vascular functional and structural changes, resulting in increased pulmonary vascular resistance and eventually right heart failure and death. Congenital Left-to-Right shunts （LTRS） is one type of congenital heart disease（CHD） and PAH associated with the congenital Left-to-Right shunt (PAH-LTRS) is a severe disease in children. However, changes in the lung microbiome and their potential impact on PAH-LTRS have not been not fully studied. We hypothesized that lung microbiota and their derived metabolites have been disturbed in children with PAH-LTRS, which might contribute to the progression and outcomes of PAH-LTRS. Methods In this study, 68 age- and sex-matched children of three different groups(patients with PAH-LTRS cohort, patients with LTRS but have no pathologic features of PAH cohort, and healthy reference cohort) were enrolled in the current study. Bronchoalveolar lavage fluid samples from these participants were conducted for multi-omics analysis, including 16S rRNA sequencing and metabolomic profiling. Data progressing and integration analysis were performed to identify pulmonary microbial and metabolic characteristics of PAH-LTRS in children. Results We found that microbial community density was not significantly altered in PAH-LTRS based on α-diversity analysis. Microbial composition analysis indicated phylum of Bacteroidetes was that less abundant while Lactobacillus, Alicycliphilus, and Parapusillimonas were significantly altered and might contribute to PAH in children with LTRS. Moreover, metabolome profiling data showed that metabolites involved in Purine metabolism, Glycerophospholipid metabolism, Galactose metabolism, and Pyrimidine metabolism were also significantly disturbed in the PAH-LTRS cohort. Correlation analysis between microbes and metabolites indicated that alterations in the microbial composition from the lung microbiota could eventually result in the disturbance in certain metabolites, and might finally contribute to the pathology of PAH-LTRS. Conclusion Lung microbial density was not significantly altered in patients with PAH-LTRS. Composition analysis results showed that the relative microbiome abundance was different between groups. Metabolome profiling and correlation analysis with microbiota showed that metabolome also altered in children with PAH-LTRS. This study indicated that pulmonary microbes and metabolites disturbed in PAH-LTRS could be potentially effective biomarkers and provides valuable perspectives on clinical diagnosis, treatment, and prognosis of pediatric PAH-LTRS.